Sisa Pembiayaan Lebih Anggaran (SiLPA) sebagai Pemoderasi antara Pajak Daerah dan Retribusi Daerah terhadap Pengalokasian Belanja Modal pada Pemerintah Daerah di Aceh - Karima, Dina; Ramadhana, Sri Winarsih (Jurnal EMT KITA, 2025)
This research aims to determine the effect of local taxes and local retributions on capital expenditure, as well as whether the Surplus Budget Balance (SiLPA) can moderate the influence of local taxes and local retributions on capital expenditure. The observation period for this study spans five years, from 2019 to 2023. The research objects are all regencies or cities in the Aceh Province. The sampling method in this study uses a non-probability sampling approach with a purposive sampling technique. This study employs secondary data obtained from the realization reports of the Regional Revenue and Expenditure Budget (APBD) recorded by the Directorate General of Fiscal Balance (DJPK) for the period 2019-2023. Data analysis is conducted using multiple linear regression analysis with the Moderated Regression Analysis (MRA) method. The findings of this study indicate that local taxes have a positive and significant effect on capital expenditure, while local retributions have a positive but not significant effect on capital expenditure. Furthermore, SiLPA is able to moderate the influence of local taxes on capital expenditure, but it is not able to moderate the influence of local retributions on capital expenditure.